Safety and efficacy of adzuki bean extract in subjects with moderate to high LDL-C: a randomized trial - Kitano-Okada, Tomoko; Nagata, Ryuji; Han, Kyu-Ho; Mikami, Nana; Satoh, Koji; Nishihira, Jun; Sasaki, Keiko; Ohba, Kiyoshi; Fukusima, Michihiro (Bioscience, biotechnology, and biochemistry, 2019)
The safety and efficacy of polyphenol-containing adzuki bean extract on lipid metabolism were evaluated in human subjects in an 8-week, randomized, double-blind, placebo-controlled, parallel intervention study. No adverse effects were observed in the participants receiving adzuki bean extract. The adzuki bean group showed a significant increase in the ΔHDL-C concentration compared with the placebo group after 4 weeks of intervention (3.76 ± 7.79 mg/dL vs. −0.08 ± 6.03 mg/dL), respectively, and both groups showed reduced ∆HDL-C concentrations, with the adzuki bean extract group showing a return to the baseline levels (0.36 ± 5.36 mg/dL) and the placebo group showing a decrease to below the baseline levels (−3.17 ± 7.79 mg/dL) at week 8. This short-term study represents the first step in establishing the practicality, safety, and plausibility of HDL-C maintaining effects of adzuki bean extract in human subjects. The safety and efficacy of polyphenol-containing adzuki bean extract were examined in human subjects using a 8-week, randomized, double-blind, placebo-controlled, parallel intervention study.